Addressing the Opioid Crisis One Surgical Patient at a Time: Outcomes of a Novel Perioperative Pain Program. (January 2020) - Shechter, Ronen; Speed, Traci J.; Blume, Erin; Singh, Sarabdeep; Williams, Kayode; Koch, Colleen G.; Hanna, Marie N.
Opioid prescriptions in the surgical setting have been implicated as contributors to the opioid epidemic. The authors hypothesized that a multidisciplinary approach to perioperative pain management for patients on chronic opioid therapy could decrease postoperative opioid requirements while reducing postoperative pain scores and improving functional outcomes. Therefore, a Perioperative Pain Program (PPP) for chronic opioid users was implemented. This study presents outcomes from the first 9 months of the PPP. Sixty-one patients met the inclusion criteria. Opioid consumption in morphine milligram equivalent (MME) was calculated and physical and health status of patients was assessed with the Brief Pain Inventory, Short-Form McGill Pain Questionnaire, and Short Form-12. Preliminary results showed significant reduction in MME, improved pain scores, and improved function for surgical patients on chronic opioids. PPP effectively reduced opioid usage without negatively influencing patient-reported outcomes, such as physical pain score assessment and health-related quality of life.